MEMBUMIKAN PENDIDIKAN KARAKTER PADA MASA PANDEMI COVID-19 - Wahyu Wahyu (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
The Covid-19 virus has plagued and infected millions of people in the world, including Indonesia. The ongoing pandemic does not only affect the health sector but also almost all areas of life. The Covid-19 virus has triggered chaos in various fields of life globally, including the field of education. Face-to-face teaching and learning activities in schools are no longer carried out and replaced with online learning. This policy was implemented to reduce the spread of the Covid-19 virus. Efforts to prevent the spread of Covid-19 in the school environment align with the government's appeal, namely to organize online learning at home. Online learning gives birth to logical consequences, both for teachers, parents, and students. Online learning brings benefits as well as challenges for teachers, parents, and students. Weaknesses that we can find in students include: (1) lack of motivation and concentration in participating in learning, (2) lack of responsibility for assignments given by the teacher, as one example, is the attitude of ignoring material and assignments, some do assignments but are collected slower even after the deadline. Normatively, this condition can be overcome with character education. A strong character in students will form a strong personality as well. In reality, our character education is currently being neglected with many dynamics of the nation. Character education is a big challenge that teachers must carry out to shape students into a better future. Character education values that need to be strengthened in the formation and development of special characters for students during the COVID-19 pandemic include (1) religious, (2) honest, (3) disciplined, (4) responsible, (5) independent, (6) curiosity, and (7) mutual respect.